2016
DOI: 10.4236/jtts.2016.64017
|View full text |Cite
|
Sign up to set email alerts
|

Crash Frequency Analysis

Abstract: Modeling highway traffic crash frequency is an important approach for identifying high crash risk areas that can help transportation agencies allocate limited resources more efficiently, and find preventive measures. This paper applies a Poisson regression model, Negative Binomial regression model and then proposes an Artificial Neural Network model to analyze the 2008-2012 crash data for the Interstate I-90 in the State of Minnesota in the US. By comparing the prediction performance between these three models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…The assumption is that exp(e) = δ has a Gamma distribution with paramters E(δ) = 1 and Var(δ) = 1/ν. The result of the combination of Poisson and Gamma distributions is the negative binomial distribution [16]. The expected value of the reponse variable is the same as the for the Poisson distribution, but the conditional variance differs:…”
Section: The Negative Binomial Regression Modelmentioning
confidence: 99%
“…The assumption is that exp(e) = δ has a Gamma distribution with paramters E(δ) = 1 and Var(δ) = 1/ν. The result of the combination of Poisson and Gamma distributions is the negative binomial distribution [16]. The expected value of the reponse variable is the same as the for the Poisson distribution, but the conditional variance differs:…”
Section: The Negative Binomial Regression Modelmentioning
confidence: 99%
“…Hence, a Poisson regression model based upon a generalized linear framework was soon adopted over conventional multiple linear regression techniques. Several such Poisson regression approaches for exploring the relationship between the risk factors and crash frequency have been proposed [15] [20]. However, it has been found that Poisson regression approaches have one important constraint that the mean must be equal to the variance which if violated, the standard errors estimated by the maximum likelihood method, will be biased, and the test statistics derived from the model will be incorrect.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, regression models need a pre-defined relationship or functional form between the dependent variable (crash frequency) and the independent explanatory variables that can be estimated by some statistical approaches, whereas the ANNs do not require the establishment of these functional forms, and can be easily applied in the analysis. On the other hand, the ANNs differ from the statistical models in that they behave as black-boxes and do not provide interpretation for the parameter estimates [15] [18] [35] [36]. Fuzzy logic applications have increasingly been proven to have a significant crash-predicting capability in recent years [49].…”
Section: Artificial Neural Network and Fuzzy Logic Modelsmentioning
confidence: 99%
“…Over-dispersion in crash data can result from a variety of factors, such as the clustering of data, unaccounted temporal correlation, and model miss-specification (Cameron and Trivedi 1998). When data are over-dispersed, estimation of a crash model can lead to biased parameter estimates, which in turn could lead to incorrect inferences regarding the factors that determine crash-frequencies [29] [30] [31] [32].…”
Section: Common Problems With Crash Datamentioning
confidence: 99%
“…theoretical) variance, and most likely to occur with small sample sizes. Although rare, however, under-dispersion can lead to incorrect parameter estimates and crash prediction [29] [31] [32] [33].…”
Section: Common Problems With Crash Datamentioning
confidence: 99%